2003
DOI: 10.1002/ctpp.200310005
|View full text |Cite
|
Sign up to set email alerts
|

Scattering processes and electrical conductivity of partially ionized hydrogen plasma

Abstract: Key words Transport properties of plasmas, strongly coupled plasmas, elementary prozesses in plasmas. PACS 52.25. Fi, 52.87.Gr, 52.20.Kn We consider partially ionized hydrogen plasma for the density region Ò ´½¼ ½ ¤ ½¼ ¾¾ µ cm ¿ . The cross sections for scattering processes between the particles are calculated within the partial wave method. Charged particles in the system (electrons, protons) interact via an effective potential that takes into account threeparticle correlations. The Buckingham polarization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
38
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…The interaction potential between the projectile electron and the screened neutral target atom is obtained by the Buckingham form of the screened effective polarization potential. 14,15 The straight-line trajectory analysis 2,3 is applied to describe the projectile motion, since the classical trajectory method has a great advantage of visualizing the bremsstrahlung radiation cross section as a function of the radiation photon energy, projectile energy, impact parameter, and plasma parameters. In Sec.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction potential between the projectile electron and the screened neutral target atom is obtained by the Buckingham form of the screened effective polarization potential. 14,15 The straight-line trajectory analysis 2,3 is applied to describe the projectile motion, since the classical trajectory method has a great advantage of visualizing the bremsstrahlung radiation cross section as a function of the radiation photon energy, projectile energy, impact parameter, and plasma parameters. In Sec.…”
Section: Introductionmentioning
confidence: 99%
“…The plasma described by the standard static DebyeHückel potential has been known as the ideal or weakly coupled classical plasma since the average interaction energy between charged particles is smaller than the average kinetic energy of a plasma particle in plasmas [8,9]. However, it is shown that the static interaction potential would not be reliable to explore the collision and radiation processes in plasmas when the velocity of the projectile is comparable to or smaller than the velocity of the plasma electron since the projectile electron would polarize the surrounding plasma shielding cloud due to the long-duration of the interaction [10]. In these circumstances, the dynamic description of the plasma electrons has to be taken into account in order to properly investigate the influence of the plasma shielding on the effective interaction potential in plasmas.…”
mentioning
confidence: 99%
“…Recently, the dynamic screening length [10] in nonideal plasmas has been obtained as a function of the velocity and temperature such as…”
mentioning
confidence: 99%
“…Hence, the expression of the bremsstrahlung crosssection [equation (11)] would be reliable to investigate the low-energy bremsstrahlung process due to the polarization interactions in nonideal plasmas. Very recently, an excellent discussion on the Gaunt factor and comparisons for the bremsstrahlung calculations by using various methods such as Born, Kramers, and Sommerfeld were given by Fortmann, Redmer, Reinholz, Röpke, Wierling, and Rozmus [16].…”
mentioning
confidence: 99%